THE ECONOMIC ROLE OF SMALL FARMS IN THE SERBIAN ECONOMY - Tošović-Stevanović, Aleksandra; Ristanović, Vladimir (The European Journal of Applied Economics, 2026)
Countries of different levels of development have different approaches to the economic importance and role of small farms. The backbone of agricultural development should be small and medium-sized farms, while large farms should create technological development and be the bearers of research in agriculture. However, in most countries, when we talk about the economic role of small farms, we are talking about a specific form of organizing agricultural production in an unfavorable market environment. For this reason, the main goal of this work is to analyze and present the position and role of small farms in the economy of Serbia, their position on the market, the environment in which they survive and the perspective of their further survival and development. For the purposes of this work, we will cite data from the latest agricultural census, public policy documents and SWOT analysis derived from available results and observations, in order to objectively list all advantages and disadvantages in order to improve the economic position of small farms in the Serbian economy.